Impact of organizational culture on voluntary employee turnover in Chinese accounting firms (OCET2040) - Zhu, Jieni (My University, 2025)
This thesis explores the impact of organizational culture on voluntary employee turnover in Chinese accounting firms by 2040. It also seeks to identify future-oriented strategies, grounded in organizational culture, to reduce employee turnover. A two-round Disaggregative Delphi study was conducted to gather expert insights. The first round consisted of a structured survey combining both qualitative and quantitative questions. Experts were asked to assess the probability and desirability of various organizational culture attributes, along with open-ended responses to elaborate on their views. Based on the first-round data, a cluster analysis was performed to group different future outlooks on organizational culture and employee turnover. This analysis resulted in four distinct images of the future. In the second Delphi round, experts reviewed these images by evaluating their probability and desirability based on their professional experience, offering a deeper understanding of potential organizational culture and their implications for employee turnover. The results indicate that organizational-oriented cultural dimensions, such as systems thinking, learning, and transparency, were seen as critical; people-oriented factors like well-being, equality, and work-life balance were rated as highly desirable yet less probable. The results of the Delphi process were organized into four future images, which provide practical insights for Chinese accounting firms seeking to address employee turnover through cultural transformation.
Keywords: organizational culture, employee turnover, Delphi method, Chinese accounting firms